Remuneração variável: uma análise econométrica com dados em painel - Sampaio Neto, Humberto da Veiga (2006)
This research work has as main objective to propose an econometrical model with panel data, validated by empirical analysis, to identify the impacts in the results of the company, after the implementation of an ample salesforce compensation program. Additionally, is intended to identify if the different social-economic profiles of the employees can bring different results with the implantation of the program. The analysis is based on a change in the wage structure of the salesforce occurred in the company in 2005. This "natural experiment" was basic for the econometrical analysis, with macroeconomic, microeconomic and social-economic variables and the introduction of the program. To the end of the empirical study, being based on research carried through in authors as Ehrenberg (2000), Robert Milgrom (1992), Misra (2005), Coughlan (1989), Lazear (2000), Basu (1985) and in the J. Macedo S/A, the main objective was achieved, in other words, it was demonstrated that the implementation of the new compensation model brought a strong positive result on the volume sold. The estimation of the coefficient of the dummy variable, representative of the implementation of the program, evidenced, with high statistic significance degree, a monthly increase of 32.8 tons in the average of the amount sold for salesman.